2019
DOI: 10.1086/699914
|View full text |Cite
|
Sign up to set email alerts
|

The Muted Consequences of Correct Information about Immigration

Abstract: Previous research shows that people commonly exaggerate the size of minority populations. Moreover, as theories of inter-group threat would predict, the larger people perceive minority groups to be, the less favorably they feel toward these groups. Here, we investigate whether correcting Americans' misperceptions of one such population -immigrants -affects attitudes toward this group. We confirm that non-Hispanic Americans over-estimate the percentage of the population that is foreign-born or that is in the U.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
182
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(199 citation statements)
references
References 42 publications
16
182
1
Order By: Relevance
“…Exclusionary attitudes-prejudice towards outgroups and opposition to policies that promote their well-being (Enos 2014)-have been implicated in political and social strife worldwide, including populist voting in the United States (Sides, Tesler and Vavreck 2018;Reny, Collingwood and Valenzuela 2019) and the resurgence of far-right political parties in Europe (Dinas et al 2019;Hangartner et al 2019). Unfortunately, previous research has found that intergroup prejudices and corresponding exclusionary political attitudes typically are strong (Hopkins, Sides and Citrin 2019;Tesler 2015), arise in the presence of even minimal group differences (Tajfel 1970), persist over time (Lai et al 2016), and are likely to further grow in response to demographic change (Velez 2018; Hajnal and Rivera 2014; Hopkins 2010; Sands and de Kadt 2019; Craig and Richeson 2014).…”
mentioning
confidence: 99%
“…Exclusionary attitudes-prejudice towards outgroups and opposition to policies that promote their well-being (Enos 2014)-have been implicated in political and social strife worldwide, including populist voting in the United States (Sides, Tesler and Vavreck 2018;Reny, Collingwood and Valenzuela 2019) and the resurgence of far-right political parties in Europe (Dinas et al 2019;Hangartner et al 2019). Unfortunately, previous research has found that intergroup prejudices and corresponding exclusionary political attitudes typically are strong (Hopkins, Sides and Citrin 2019;Tesler 2015), arise in the presence of even minimal group differences (Tajfel 1970), persist over time (Lai et al 2016), and are likely to further grow in response to demographic change (Velez 2018; Hajnal and Rivera 2014; Hopkins 2010; Sands and de Kadt 2019; Craig and Richeson 2014).…”
mentioning
confidence: 99%
“…Much of the persuasion literature focuses on ways to influence consumer or political preferences. Closer to our work are studies on attitude change about intimate partner violence (Gupta et al, 2013;Abramsky et al, 2014;Pulerwitz et al, 2015;Green et al, 2020), racial minorities (Donovan and Leivers, 1993), immigrants (Hopkins et al, 2019;Grigorieff et al, 2020), and women in STEM (Moss-Racusin et al, 2018), as well as studies that shift people's perceptions of social norms about gender or about ethnic discrimination and violence (Bursztyn et al, 2020;Aloud et al, 2020;Paluck, 2009).…”
mentioning
confidence: 99%
“…A brief experience may not impact left partisans but reinforce the perception that outsiders are threatening which is associated with resistance towards change (Homola and Tavits 2017). More generally, recent evidence suggests that inaccurate perceptions about the size of foreign-born populations are a consequence of anti-refugee attitudes, and not their cause (Hopkins, Sides, and Citrin 2018). Thus, citizens who are sceptical towards immigration may experience the refugee crisis as more threatening.…”
Section: Hypothesis 2 (H2)mentioning
confidence: 99%